Dinamika Antargenerasi dalam Pendidikan Anak Pemulung di Kawasan TPA Supit Urang - Saif Saiful Nur Kholis; Meiji Nanda Harda Pratama (Dimensia: Jurnal Kajian Sosiologi, 2026)
Education plays a vital role in improving quality of life; however, access to education remains a challenge for some scavenger communities in TPA Supit Urang. This study explores intergenerational educational dynamics by examining the roles of families, communities, and educational institutions in shaping children's understanding of education. Using a phenomenological qualitative approach, this research involved 10 informants, including scavenger families, community leaders, and local school principals. The findings indicate that low educational participation among scavenger children is influenced not only by economic factors but also by cultural norms, social mindsets, and the lack of support from both the community and educational institutions. Therefore, a multi-level intervention involving families, communities, schools, and the government is necessary to create more inclusive educational access and break the cycle of poverty within the scavenger community. Keywords: scavenger education, intergenerational, dynamics poverty cycle